The Correlation between Students Mindset and Speaking Skill: A Correlational Study - Nurraida Nurraida; Nurul Muharrami (English Teaching and Linguistics Journal (ETLiJ), 2022)
The thesis entitled The correlation between students mindset and speaking skill (A Correlational Research at Ninth grade students of MTsN Aceh Utara). There are four skills in English; listening, speaking, writing and reading. Among four skills in English, speaking is most dreaded form in communication and it is difficult to be mastered in learning a new language. In mastering speaking was not enough only by being expert in grammar, listening, reading and have a lot of vocabularies, because there are a lot of students who have the skill mentioned above but they do not have good performance in speaking because they afraid to apply their speaking ability in front of colleague and its all may caused they do not have good mindset. The problem of this research was: Is there any significant correlation between students mindset and their speaking skill?. The purpose of this research was to find out whether there is significant correlation between students mindset and speaking skill. To conduct the research, correlational research was used, this research used to measure two variables. The population was ninth grade students of MTsN 6 Aceh Utara. the sample of this research was 32 students, 30 % of the whole ninth grade students, they were taken randomly. The instrument used were questionnaire to measure students mindset and test to measure students speaking ability. The result of data analysis showed that the correlation coefficient was 0,86, it was found in index correlation score of 0,60 1,799 was in the strong degree. The result of t-test (4,74) was higher than t-table in significance 0,05 (2,042). Based on the research result, the researcher concluded that there was any significant correlation between students mindset and speaking skill.